Macro-meso dynamic analysis of railway transition zone: Hybrid DEM/FDM simulation and experimental validation. Issue 135 (August 2020) - Shi, Can; Zhao, Chunfa; Yang, Yang; Guo, Yunlong; Zhang, Xu; Feng, Yang
Abstract: To probe into the mechanical behaviour of railway transition zone from the macro-meso aspects, a numerical model of transition zone is built that hybrids the Discrete Element Method (DEM) and Finite Difference Method (FDM). The DEM is utilised to simulate the ballast bed and sleeper, because it can consider the realistic ballast shapes and complex contacts between them. The FDM based on the continuum theory is utilised to simulate the track substructure according to a real structural form. Afterwards, the coupling algorithm is used to achieve the hybrid DEM-FDM simulation. The engineering practicality of this model is validated using the dynamic responses of the transition zone from a field measurement, and the macro-meso mechanical behaviour of the transition zone is analysed with or without the wedge-shape backfill. The numerical results indicate that applying the wedge-shape backfill can considerably reduce the sudden changes of track vibration and substructure surface stresses at the vicinity of the connection between the structure and embankment. Moreover, the mesoscopic results show that the acceleration vector of the soil near the rigid structure fluctuates towards the embankment and the velocity responses of track components and substructure increase gradually when the train travels from the rigid structure to the soft embankment. Highlights: Establish track transition models by combining DEM with FDM. Ballast particles are accurately depicted from mesoscopic level. Field measurements are conducted to validate this coupled model. The macro-meso mechanical behaviours of transition zones are analysed. Evaluate the wedge-shape backfill effect on dynamic performance of track transitions.